Bremsstrahlung polarization correlations and their application for polarimetry of electron beams - Tashenov, Stanislav; Bäck, T.; Barday, R.; Cederwall, B.; Enders, Joachim; Khaplanov, A.; Fritzsche, Yu.; Schässburger, K.-U.; Surzhykov, Andrey; Yerokhin, Vladimir; Jakubassa-Amundsen, D. (Physical review. A, Atomic, molecular, and optical physics, 2013)
Linear polarization of hard x rays emitted in the process of atomic-field electron bremsstrahlung has been measured with a polarized electron beam. The correlation between the initial orientation of the electron spin and the angle of photon polarization has been systematically studied by means of Compton and Rayleigh polarimetry techniques applied to a segmented germanium detector. The results are in good agreement with those of fully relativistic calculations. The observed correlations are also explained classically and in a unique way manifest that due to the spin-orbit interaction the electron scattering trajectory is not confined to a single scattering plane. The developed photon polarimetry technique with a passive scatterer is very efficient and accurate and thus allows for additional applications. Bremsstrahlung polarization correlations lead to an alternative method of polarimetry of electron beams. Such a method is sensitive to all three components of the electron spin. It can be applied in a broad range of the electron beam energies from ≈100 keV up to a few tens of MeV. The results of a measurement at 100 keV are shown. The optimum scheme for electron polarimetry is analyzed and the relevant theoretical predictions are presented.
Gesehen am 31.01.2022